Ambidextrous Green Human Resource Management and Employee Green Creativity in Eco-Tourism Homestays: The Mediating Role of Green Knowledge Sharing - Agus Setiono; Agus Suroso; Dwita Darmawati (Fundamental and Applied Management Journal, 2026)
This study investigates how ambidextrous green human resource management (AGHRM) fosters employee green creativity (EGC) in eco-tourism homestays, with green knowledge sharing (GKS) as a mediating mechanism. Drawing on ambidexterity theory, this study addresses the dual challenge faced by small-scale eco-tourism enterprises in balancing environmental compliance with sustainable service innovation.Using survey data from 300 employees around GunungLeuser National Park, the model was tested using partial least squares structural equation Modelling (PLS-SEM). The results show that AGHRM significantly enhances GKS, which in turn positively influences EGC, while the direct effect of AGHRM on EGC is not significant, indicating an indirect-only mediation effect. These findings provide empirical support for the application of ambidexterity theory to explain employee-level environmental creativity through knowledge-sharing processes.This study highlights the importance of structured knowledge sharing in translating green HRM practices into employee creativity in eco-tourism homestays.